Around the world in 30 programs: a framework for integrating culture in a retail loyalty program - Franchim, Debora (2024)
This paper proposes a framework to incorporate national culture in retail loyalty programs as a tool to increase its adherence to the audience and increase its results. Multiple quantitative studies have proven that culture impacts loyalty, but a framework on how to do it hasn’t been yet presented. Document analysis of 75 program terms and conditions and communication pieces was combined with interviews of 17 loyalty executives in five different countries, connecting their programs characteristics with their country’s cultural dimensions, using Schwartz’s cross-cultural scores. The result is a practical framework to support managers into integrating culture into their loyalty programs, by incorporating it in the consumer needs phase, the analysis of benchmarks, the design of the program and in its communication.